PEMANFAATAN POJOK BACA DALAM MENANAMKAN MINAT BACA SISWA KELAS 4 DI SDK NUABOSI - Maria Yulianti Tai; Elisabeth Tantiana Ngura; Yasinta Maria Fono (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Reading interest is a person's passion or interest in being able to interpret media words with the aim of obtaining the information needed. This research is motivated by the utilization of the reading corner in instilling students' interest in reading in class 4 SDK Nuabosi. The purpose of this study is an effort to maintain a culture of literacy by utilizing the reading corner in instilling interest in reading among 4th grade students of SDK Nuabosi. This research uses a qualitative descriptive method. The data collection techniques used were observation, interview and documentation. Based on The results showed that the utilization of the reading corner plays an important role in fostering interest in reading. The utilization of the reading corner in fostering students' interest in reading at SDK Nuabosi is carried out in several ways, namely the reading corner is designed as good as possible, the books are neatly arranged, there are story books or textbooks